Preventive prison and punitive populism: study of the divergence between student perception and legal doctrine in Peru - Vasquez, Lorena (2026)
Pretrial detention constitutes one of the most controversial institutions within the Peruvian judicial system. Doctrinally, it is conceived as an exceptional precautionary measure; however, in public debate it is often understood as a mechanism of anticipatory punishment. This study analyzes the divergence between the guarantee-based model developed by legal doctrine and the perception of non-law university students at the Universidad Tecnologica del Peru. A qualitative, descriptive, documentary, and empirical methodology was employed, based on semi-structured interviews and comparative analysis with the doctrinal framework. The findings reveal that most participants associate pretrial detention with an immediate response to crime, influenced by media discourse and public security demands. The study concludes that a process of social resignification is taking place, exposing a gap between its precautionary legal nature and its understanding outside the technical sphere, thereby posing challenges to judicial legitimacy.